Elements of Optimizing User Engagement in E-Commerce Website - Rosclaritha Maidom L.; Baharum A.; Ismail R.; Fatah N.S.A.; Omar M.; Noor N.A.M. (Springer Science and Business Media Deutschland GmbH, 2023)
Reliability analysis; Reliability theory; User interfaces; Web Design; Cognitive; Competitive environment; Design elements; E-commerce websites; Theoretical foundations; User driven; User engagement; User oriented; Users' experiences; Value co creations; Electronic commerce